Análise estrutural sobre a atividade biológica de um derivado de Tioxopirimidina - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Small molecules are the main substances that regulate protein inhibition in organisms. Within this group, thioxopyrimidines stand out for having bioactive derivatives and because of the wide variety of analogues that have not yet been identified. In the study of these compounds, crystallography presents itself as an important methodology for being able to accurately describe the arrangement of atoms and molecules in the crystal, which makes it possible to infer about their physical and chemical properties and simulate their affinity with the active site of proteins. In this work, the compound ethyl 4-methyl-2-phenyl-6-thioxo-1,6-dihydro-5-pyrimidinecarboxylate (MP-TDPy) was studied in order to determine its crystal structure, identify and quantify its main intermolecular interactions, analyze their conformation, theoretically evaluate their reactivity and evaluate possible structural modifications for the development of new molecules with biological potential. For this, the crystallographic methodology will be used from single crystal X-ray diffraction, analysis of the Hirshfeld surface, comparisons of conformations in the crystal and in the protein binding site, theoretical calculations of geometric optimization, frontier molecular orbitals and molecular electrostatic potential, in addition to molecular docking. Crystallographic analysis suggests that its crystal structure is stabilized by hydrogen bonds coordinated by water molecules, in addition to C—H···S and π-π interactions. The docking results show a reasonable accommodation of the molecule at the topoisomerase IV binding site and interact mainly by hydrogen bonds between the thioxopyrimidine portion with Glu198, Thr292, and Gly225, aided by hydrophobic interactions involving the rest of the molecule. These results suggest a relationship between the antibacterial activity shown and the 4-thioxopyrimidine portion, leading to the investigation of new compounds that use this scaffold.
Structural analysis on biological activity of a Thioxopyrimidine derivative
Keywords: Tioxopirimidinas; Difração de raios X; Superfície de Hirshfeld; Thioxopyrimidines; X-ray diffraction; Hirshfeld surface; QUIMICA::FISICO-QUIMICA